MULTIKULTURALISME : SEBAGAI SOLUSI MENEKAN KONFLIK DALAM ORGANISASI - Wayan Arya Paramarta (Forum Manajemen STIMI Handayani Denpasar, 2012)
Conflicts on some organization probably happened, meanwhile we have many employees coming from multi cultures such as: different of ethnicty, religions,cultures, gender and other uniqly differences which every people had. Therefore,every companies owners or manager have to improved their employees ability, whichcoming from multi cultures background, so they can work in different environmentand combine that differences become a good and strong corporations and company’sowner or manager have to solved and finished any kinds of conflict, which potentialshappened while the employees working on differences.